The Knowledge Level of Pregnant Mothers About Preeclamsia at The Clinic in Tondano Minahasa Regency - Herlina Sarista Simanjuntak; Jelica Jenifer Rotinsulu; Veronika Ani Wulandari; Joice Cathryne; Mega Tri Anggraini (Journal of Nursing Science Update (JNSU), 2023)
Preeclampsia is a health problem that is often found in pregnant mothers. Indonesia has 76.000 women and 500.000 infant deaths caused by preeclampsia every year. Based on an interview with a nurse clinic in Tondano Minahasa Regency, 25 of 50 women during pregnancy have preeclampsia. This study aimed to find the knowledge level of pregnant mothers about preeclampsia at a Clinic in Tondano Minahasa Regency. This study used a descriptive quantitative method with a univariate data analysis technique. The sample of this study is 50 pregnant women willing to be respondents and registered at Clinic in Tondano Minahasa Regency with accidental sampling as the sampling method. The instrument of this study uses a questionnaire about the knowledge level of pregnant mothers about preeclampsia. The result of this research shows that 35 (70%) pregnant mothers had good knowledge, 11 (22%) pregnant mothers had a moderate amount of knowledge, and 4 (8%) pregnant mothers had insufficient knowledge about preeclampsia. Institutions can use the results of this study to increase pregnant mothers' knowledge about preeclampsia through education, and it can also be used as overview knowledge about preeclampsia for the public. Future research can use this study as a reference for prospective studies about the incidence of preeclampsia with different variables.